Are Cybersecurity Laboratory Exercises Constructivist in Use? (Journal of The Colloquium for Information Systems Security Education, 2014)
Private industry and U.S. government entities alike have expressed urgent demand for employable students with practical experience in cybersecurity. In response, education increasingly utilizes laboratory exercises as part of an overarching pedagogy. To date, the design and implementation of such exercises has purportedly been of a constructivist nature. As such, prominent learning theory maintains that students are at the center of knowledge acquisition. A body of research supports this notion. However, a gap exists in the literature insofar as there has been no examination of how these exercises manifest learning theory when in use. Therefore, the purpose of this study was to measure how users of cybersecurity laboratory exercises describe those exercises, in use, in the context of learning theory. Through a mixed method approach, data revealed that users describe the exercises as objectivist in nature. Such a result is significant for educators and researchers. Further, based on the results, this study includes several recommendations for future work.
Keywords: cybersecurity; laboratory exercises; pedagogy; constructivism; objectivism